STUDI KELAYAKAN BISNIS LAPANGAN FUTSAL DI KOTA BATAM - Sidabutar, Joel Alexander; Asmarawati, Citra Indah (Computer Science and Industrial Engineering, 2024)
The development of the business world today has experienced very rapid progress. Anyone can start a business to improve their lives economically and socially. Business is all activities that are generally planned and carried out by individuals or groups with the aim of producing, promoting, and selling goods and services, whether for profit or not. Futsal is a sport that is currently popular in various big cities. Futsal is an indoor or outdoor football sport played by two teams of five players each. The growth and interest in futsal has opened up business opportunities for small and medium enterprises engaged in services. Futsal businesses can offer various types of businesses apart from futsal rentals. Seeing that, the potential of the futsal business market becomes very promising, so the growth of futsal facilities in various cities shows high demand where people want to play and practice futsal regularly. So that the need for this futsal field has been evenly distributed throughout Indonesia, one of the locations where there are several futsal courts is in Batam City, namely Planet Futsal. There are many challenges faced by Planet futsal SMEs in managing this business, so a business feasibility study is needed so that this business can survive and increasingly show the potential success of a futsal field rental business. This feasibility analysis is carried out to ascertain whether or not a business activity is feasible based on financial and non-financial. aspects A business feasibility study is carried out to ensure the feasibility of a business activity based on several aspects. In general, the aspects analyzed are market and marketing feasibility, legal feasibility, management and human resource feasibility, and technical and technological feasibility. Based on the results and discussion, conclusions were obtained in this study, namely on market and marketing aspects in market potential, market share, products, prices, promotions, places are available / feasible. In the aspects of management and human resources, it has been structured in the organization and also the schedule of working hours that have been set. In the legal aspect, this business is feasible to run because it has complete supporting documents as a condition for running a business. In technical and technological aspects, this business is already located in the desired target market, access to the field is also easy to find, and the layout is in accordance with the flow.